2019
DOI: 10.52728/ijjm.v1i1.31
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Marketing Strategy and Service Quality Against the Decisions of Parents

Abstract: This study aims to analyze and determine the effect of marketing strategy variables and service quality on parents' decisions. In this study, the dimensions of marketing strategies include products, prices, promotions, places, people, processes and physical evidence. Service quality dimensions include reliability, responsiveness, confidence, empathy and tangibility. Quantitative methods with multiple linear regression analysis were processed using SPSS for windows version 22. The results showed that there were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…With the research findings, the hypothesis can be accepted because capital structure and profitability have a considerable relationship. This finding is consistent with the results of research conducted by (DHINATA, 2020) and (Amelia et al, 2019), which showed that having a low level of debt can reduce the risk of bankruptcy for companies. By managing funds efficiently and trying to increase the company's cash inflow, the company can reduce these risks so as not to go bankrupt.…”
Section: Effect Of Capital Structure (X1) On Profitability (Y1)supporting
confidence: 92%
“…With the research findings, the hypothesis can be accepted because capital structure and profitability have a considerable relationship. This finding is consistent with the results of research conducted by (DHINATA, 2020) and (Amelia et al, 2019), which showed that having a low level of debt can reduce the risk of bankruptcy for companies. By managing funds efficiently and trying to increase the company's cash inflow, the company can reduce these risks so as not to go bankrupt.…”
Section: Effect Of Capital Structure (X1) On Profitability (Y1)supporting
confidence: 92%
“…By providing quality services, it will create a positive perception from customers and will lead to satisfaction after experiencing the services provided. The results of this study are in accordance with and in line with (Amelia, Salamah, & Sofyan, 2019) which states that marketing strategy has a positive effect on service quality.…”
Section: Marketing Strategy On Service Qualitysupporting
confidence: 89%
“…In addition, analyze the main factors of the business's product that can convert parents into customers of the business's product (Amelia et al, 2019).…”
Section: How Does Neuromarketing Affect Parents' Decisions?mentioning
confidence: 99%